2017
DOI: 10.7287/peerj.preprints.3279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of sympatric Platanthera bifolia and Platanthera chlorantha (Orchidaceae) populations with intermediate plants

Abstract: Platanthera bifolia and P. chlorantha are terrestrial and rewarding orchids with a wide Eurasian distribution. Although genetically closely related, they exhibit significant morphological, phenological and ecological differences that maintain reproductive isolation between the species. However, where both species co-occur, individuals with intermediate These results are corroborated also by floral scent analyses, which confirmed a strong similarity in floral scent composition between intermediate morphotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Buttler (2011) distinguished the two taxa at species level, and following studies in Belgium (Esposito et al 2016, 2017, 2018, Ambroise et al 2019), his disposition was supported by Tyteca and Esposito (2018). According to Jonsell (2004: 163): ‘Taxa are treated as species if they differ in at least two presumably independent morphological characters and are more or less completely separated by a barrier – geographical and/or ecological, phenological or genetic.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Buttler (2011) distinguished the two taxa at species level, and following studies in Belgium (Esposito et al 2016, 2017, 2018, Ambroise et al 2019), his disposition was supported by Tyteca and Esposito (2018). According to Jonsell (2004: 163): ‘Taxa are treated as species if they differ in at least two presumably independent morphological characters and are more or less completely separated by a barrier – geographical and/or ecological, phenological or genetic.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the short-spurred and long-spurred taxa can be aptly characterized as less prominent ecological variants that largely differ from each other in a few characters. Moreover, the circumstance that the short-spurred taxon seems to have an incoherent distribution comprising 1) Atlantic NW Europe, 2) the Alps, 3) Portugal and 4) Toscana (Buttler 2011, Tyteca andEsposito 2018) suggests that this taxon might be polyphyletic -especially when taking into account the evolutionary role of pollinator shifts in P. bifolia s.l. (Boberg et al 2014).…”
Section: Taxonomic Rankingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study performed in Sweden showed the presence in the aroma of methyl benzoate, benzyl acetate, benzyl benzoate, benzyl salicylate, and lilac aldehydes Orchids from Basilicata: The Scent [29]. Finally, in a work performed in Belgium, 3,7-dimethyl-1,3,6-octatriene, and santolinatriene were detected in the aroma [30].…”
mentioning
confidence: 94%
“…In Switzerland, linalool, methyl benzoate, and geraniol were the components of the aroma [27,28]. In Pays-Bas, lilac aldehydes and linalool were found [28]; in Sweden, methyl benzoate and linalool [28]; and in Belgium, the main components were 3,7-dimethyl-1,3,6-octatriene, 3carene, and lilac aldehyde [30].…”
mentioning
confidence: 99%